Crop growth analysis and yield of a lignocellulosic biomass crop (Arundo donax L.) in three marginal areas of Campania region - Impagliazzo, Adriana; Mori, Mauro; Fiorentino, Nunzio; Di Mola, Ida; Ottaiano, Lucia; De Gianni, Donato; Nocerino, Sabrina; Fagnano, Massimo (Italian Journal of Agronomy, 2017)
The depletion of energy resources from fossil fuels and global warming have pushed to consider the agro-energy as one of the renewable energy sources for mitigation of climate change. In this context, agro-energy based on cultivation of energy crops in marginal lands allows to reduce competition with food crops and marginal lands abandonment, producing incomes for farmers. The aim of this work is to improve the knowledge on a promising crop (Arundo donax L.) for the production of bio-energy in marginal lands. Therefore, the behaviour of this crop was evaluated in three study areas of Campania region, under different energy inputs: two levels of nitrogen fertilisation, N100 and N50 in Sant’Angelo dei Lombardi (SA) and Bellizzi (BL). In Acerra (AC) site compost fertilisation was made to verify its effect on pollutant phytoextraction. In the last year, also crop growth analysis was done in the three sites. The results showed that giant reed confirms its adaptability to low fertility soils, allowing interesting biomass yield also in marginal lands. In more fertile environments, effect of fertilisation is not significant at least in the short term. Nevertheless, nitrogen uptake (65-130 kg N ha–1), also if lower than other highyielding crops, needs to be compensated with fertilisation to avoid depletion of soil nutrient reserves and to guarantee sustainability of this cropping system. Giant reed had a positive environmental impact, due to the improvement in soil fertility (soil organic matter and nitrogen increase) and to the mitigation of climate change (C storage in the soil). In marginal soils of Southern Italy this crop confirms an increasing trend of yield during the first 3-4 years. High productivity levels of this crop are related to the extremely high duration of the vegetative period and thus of the photosynthetic activity (from March to November in the Mediterranean area). These last are well expressed by the leaf area duration index, which is more than double than other high-yielding crops such as maize (280 vs 140 days).